Gender Differences in the Psychosocial Functioning of Parents During the COVID-19 Pandemic - O’Sullivan, Katriona; Rock, Nicole; Burke, Lydia; Boyle, Neasa; Joksimovic, Natasha; Foley, Holly; Clark, Serena (Frontiers in Psychology, 2022)
The Covid-19 pandemic affected all aspects of society; families now live, work, and educate in one place with little external interactions. This research aimed to understand how Covid-19 has affected gender imbalances in the home by considering home-schooling as an extra task for families. Previous research shows that mothers carry more family responsibilities than fathers and in turn can experience higher levels of stress. This study employed a quantitative cross-sectional online survey to extend our understanding of the interaction between homeschooling, work and home life, and stress levels in a group of 364 parents. In total 232 mothers and 132 fathers completed the survey and results revealed mothers were 10 times more likely to be responsible for home-schooling than fathers, and 44% of mothers felt they had no help with home-schooling and were generally more stressed than fathers. These results show that lack of supports, having to manage home-schooling, and being a mother predicted increased stress. 10% of mothers reported leaving their jobs due to pressure added by home-schooling. This study broadens the understanding of the pandemics impact on gender imbalances in family responsibilities and emphasizes the need for extra consideration for the impact on mothers as we emerge from this pandemic.